Educational Expansion, Skills Diffusion, and the Economic Value of Credentials and Skills - Araki, Satoshi (American Sociological Review, 2020)
Examining the economic value of education has been a central research agenda of social scientists for decades. However, prior research inadequately accounts for the discrepancy between educational credentials and skills at both the individual and societal levels. In this article, I investigate the link between credentials, skills, and labor market outcomes against a background of societal-level educational expansion and skills diffusion. Using internationally comparable OECD data for approximately 30,000 individuals in 26 countries, I find that both credentials and skills generally contribute to occupational and monetary rewards. In particular, the premium for credentials far outweighs that for skills. This is in contrast to recent arguments that skills are the key to economic success. Nevertheless, returns to credentials decline in tandem with educational expansion, whereas skills retain their premium even as they diffuse in a given society. Furthermore, skills diffusion also leads to the diminishing monetary return to high credentials. These findings suggest that skills diffusion promotes more meritocratic reward allocation via devaluing high credentials without explicit depreciation of high skills.